H2O2 based α-pinene oxidation over Ti-MCM-41. A kinetic study - Cánepa, Analía Laura (2011)
α-Pinene oxidation with hydrogen peroxide using Ti-MCM-41, prepared by hydrothermal synthesis, with a Ti content of 1.12 wt.% was studied. The major products of reaction observed were: verbenone, verbenol and campholenic aldehyde which are used in the pharmaceutical, perfume and cosmetics industry. The effects of various parameters such as the concentration of reagents, catalyst and temperature on the reaction rate have been studied. The experimental results show that the surface chemical reaction onto the catalytic site controls the overall reaction rate. A kinetic model that includes the absorption of reactants, water and solvent on the catalyst was proposed. The analysis of the initial rates allowed to determinate that the reaction is first order regarding to the α-pinene, hydrogen peroxide and catalyst amount and zero order with respect to H2O, with apparent activation energy of 67.5 kJ/mol. Under the study conditions, leaching of the active species is not observed. Finally, the catalyst can be used repeatedly without losing activity or selectivity, confirming that the reaction proceeds through a certainly heterogeneous process. © 2011 Elsevier B.V. All rights reserved.